EVALUACIÓN DE UNA TÉCNICA FÍSICO-MATEMÁTICA PARA LA ESTIMACIÓN DE LLUVIAS EXTREMAS DURANTE EL PERIODO EL NIÑO DÉBIL A MODERADO 2002 - Fashé Raymundo, O. (2005)
The goal of the present paper ís the evaluation of a physical-mathematical technique to estímate the rain rate in the Peruvian north coast during days of extreme rainfall the period considered in this work in april 2002. For this purpose infrared GOES-8 satellíte images have been used. The results show that the used technique produces a good representation of the diurna!varíability of rain; however a seríous deficiency exísts in the daily rain rate estimation. The orography conditions and rapid rain formation during an atmospheric process similar to EL NIÑO one would explaín the cause of the opposing results.